ACCESS TO “INTERNATIONAL JUSTICE” (THE JURISDICTION OF INTERNATIONAL COURTS) IN THE CASES OF ENVIRONMENTAL PROTECTION - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
This paper deals with the issue of jurisdiction of international courts and tribunals for resolving disputes in the field of environmental protection. In the last few decades there was intense activity of states in the regulation of this field and in achieving this goal numerous international treaties have been concluded. In the cases of their violations there should be an international forum which would resolve this kind of disputes. In this moment there are some courts, tribunals and arbitrations which could resolve environmental disputes. However, these are not specialized courts but under their general competencies they can deal with these disputes. The problem is that States have to accept their jurisdiction, which means that jurisdiction is not compulsory. Also, the private entities do not have the right to access these instances. Courts and committees for the protection of human rights have their role in the environmental protection. The Court of Justice of the EU has made a significant progress in enforcing environmental rules, due to its specific position and competencies given to it by the founding treaties of the European Union. The shortcomings of the existing mechanisms for dispute resolution could be avoided by creating a specialized International Court for Environment, but the procedure for its creation is still in progress and it is uncertain whether it will be established or not.